Global ecosystems and fire: Multi‐model assessment of fire‐induced tree‐cover and carbon storage reduction. (27th June 2020) - Lasslop, Gitta; Hantson, Stijn; Harrison, Sandy P.; Bachelet, Dominique; Burton, Chantelle; Forkel, Matthias; Forrest, Matthew; Li, Fang; Melton, Joe R.; Yue, Chao; Archibald, Sally; Scheiter, Simon; et al.
Abstract: In this study, we use simulations from seven global vegetation models to provide the first multi‐model estimate of fire impacts on global tree cover and the carbon cycle under current climate and anthropogenic land use conditions, averaged for the years 2001–2012. Fire globally reduces the tree covered area and vegetation carbon storage by 10%. Regionally, the effects are much stronger, up to 20% for certain latitudinal bands, and 17% in savanna regions. Global fire effects on total carbon storage and carbon turnover times are lower with the effect on gross primary productivity (GPP) close to 0. We find the strongest impacts of fire in savanna regions. Climatic conditions in regions with the highest burned area differ from regions with highest absolute fire impact, which are characterized by higher precipitation. Our estimates of fire‐induced vegetation change are lower than previous studies. We attribute these differences to different definitions of vegetation change and effects of anthropogenic land use, which were not considered in previous studies and decreases the impact of fire on tree cover. Accounting for fires significantly improves the spatial patterns of simulated tree cover, which demonstrates the need to represent fire in dynamic vegetation models. Based upon comparisons between models and observations, process understanding and representation in models, we assess a higher confidence in the fire impact on tree cover and vegetation carbon compared to GPP, total carbon storage and turnover times. We have higher confidence in the spatial patterns compared to the global totals of the simulated fire impact. As we used an ensemble of state‐of‐the‐art fire models, including effects of land use and the ensemble median or mean compares better to observational datasets than any individual model, we consider the here presented results to be the current best estimate of global fire effects on ecosystems. Abstract : This is the first multi‐model assessment of the influence of fire on vegetation and the carbon cycle under current climate and land use conditions. The influence of fire is derived by comparing a model simulation with fire to a simulation without fire. Based upon comparisons between models and observations, process understanding and representation in models, we assess a higher confidence in the fire impact on tree cover and vegetation carbon compared to vegetation productivity, total carbon storage and turnover times.